Thermal performance and fitness of glacial till for Rammed Earth construction - Pavia, Sara (My University, 2019)
The search for sustainability caused a revival of earth construction. Rammed earth (RE) construction is often preferred as compaction and stabilization leads to stronger, more consistent materials. Tills are glacial sediments. Historically, they were used for construction and brick making. However, their heterogeneous nature has prevented standardisation into mainstream construction. This work contributes to make earth a reliable building material. It evaluates the suitability of till for RE construction by measuring its geotechnical parameters and comparing them against recommended RE values. The results are consistent with other tills and indicate fitness for RE construction. The tills were successfully stabilized with 5% lime, reaching compressive strengths c.1.09 MPa. Thermal performance is vital in construction. High thermal mass materials such as RE can lower today's unsustainable energy demand for heating and cooling. This work experimentally measures the thermal properties of the till and compares them to other constructions. The experimental values are feed into models to compare thermal performance against other REs and concretes. The rammed till has high conductivity (1.65 W/m K) and specific heat capacity (1218.66 J/kg K) indicating a substantial scope to store heat and poor insulation ability. The thermal diffusivity (7.42 × 10–7 m2/s) suggests that the till will impede heat flow to a greater extent than concrete. In the simulations, the RE assemblies showed the thermal lag typical of high thermal mass materials reducing the fluctuations of external temperature and increasing the internal thermal stability when compared with concrete. All insulated assemblies maintained thermal comfort indexes however, the RE assemblies performed slightly better than concrete; in particular the internally insulated RE, with longer times in superior comfort indices and the smallest temperature drops. The annual heat load of insulated RE is 2–4.2% lower than the concrete construction.
PUBLISHED
https://doi.org/10.1016/j.jobe.2019.02.019
Keywords: Earth construction; Rammed till; Thermal properties; Thermal lag; Heating load; Comfort index; Smart & Sustainable Planet